How does justice in value chains influence farmer wellbeing? Evidence from the Peruvian cocoa sector - Bruelisauer, Samuel; Zavaleta, Diego; Montoya-Zumaeta, Javier Gustavo; Jacobi, Johanna (Frontiers in Sustainable Food Systems, 2025)
Improving farmer wellbeing presents a key focus for improving the sustainability in cocoa value chains, both as a goal in itself and given the role of farmers as key agents in wider sustainability transformations. While evidence on the effects of private sustainability governance strategies abounds, much less is known about the causal mechanisms producing or inhibiting such effects. Research in organizational psychology and management studies points to the importance of whether farmers feel treated in a fair manner by their buyers and the extent to which such fairness and justice are institutionalized in governance strategies. Our study therefore draws on theoretical insights from the interdisciplinary justice literature to develop hypotheses on the role of distributive, procedural and recognition justice in moderating wellbeing effects in key private sustainability governance strategies: cooperatives, corporate sustainability programmes, and social entrepreneurship. We conduct process tracing utilizing both qualitative and quantitative data to compare three case studies in a main cocoa producing region in the Peruvian Amazon. Our results support the hypothesized positive influence of justice attributes in all three dimensions as we elicit distinct causal mechanisms through which practices institutionalizing distributive, procedural and recognition justice enhance farmers’ wellbeing, satisfaction and commitment. In contrast to some earlier work, the results suggest that most farmers consider distributive attributes as more important than procedural or recognitional elements. An emergent theme from the research further suggests that farmers expectations in terms of just treatment are differentiated by the type of buyer, with cooperatives being held to a higher standard than private companies.